2018
DOI: 10.2337/dc18-0343
|View full text |Cite
|
Sign up to set email alerts
|

Sotagliflozin in Combination With Optimized Insulin Therapy in Adults With Type 1 Diabetes: The North American inTandem1 Study

Abstract: In a 1-year T1D study, sotagliflozin combined with optimized insulin therapy was associated with sustained HbA reduction, weight loss, lower insulin dose, fewer episodes of severe hypoglycemia, improved patient-reported outcomes, and more DKA relative to placebo (ClinicalTrials.gov, NCT02384941).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
287
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(309 citation statements)
references
References 41 publications
17
287
1
4
Order By: Relevance
“…ClinicalTrials was also searched and no additional clinical trials with reported results could be found. Finally, in total, 13 eligible studies with 5397 participants (3364 participants in intervention groups vs 2033 participants in control groups) were enrolled, including two articles in one RCT for canagliflozin, four articles for dapagliflozin, four articles for empagliflozin (three articles in one RCT) and six articles for sotagliflozin . Most of the articles showed a relative low risk bias, but other bias with a higher risk was because nine studies were funded …”
Section: Resultsmentioning
confidence: 99%
“…ClinicalTrials was also searched and no additional clinical trials with reported results could be found. Finally, in total, 13 eligible studies with 5397 participants (3364 participants in intervention groups vs 2033 participants in control groups) were enrolled, including two articles in one RCT for canagliflozin, four articles for dapagliflozin, four articles for empagliflozin (three articles in one RCT) and six articles for sotagliflozin . Most of the articles showed a relative low risk bias, but other bias with a higher risk was because nine studies were funded …”
Section: Resultsmentioning
confidence: 99%
“…This is in line with recent studies showing an association between patients' glycaemic status and weight loss, 39 and may result from higher levels of Total GTL P-Levels of incretin hormones, GLP-1, PYY 3-36 and GIP following treatment with licogliflozin in patients with T2DM. Multiple clinical studies have been conducted to assess the efficacy and safety of sotagliflozin in patients with diabetes 26,[43][44][45]. (n = 15/cohort).…”
mentioning
confidence: 99%
“…She challenged the DKA protocols used in SGLT‐2 inhibitor clinical trials: (a) inTandem for sotagliflozin, (b) Dapagliflozin Evaluation in Patients with Inadequately Controlled Type 1 Diabetes (DEPICT) for dapagliflozin, and (c) Empagliflozin as Adjunctive to Insulin Therapy (EASE) for empagliflozin, stating that they did not adequately emphasize DKA prevention. This opinion was based on these trial protocols' high baseline HbA1c ranges and lack of exclusion criteria based on baseline beta‐hydroxybutyrate levels . Dr Peters' personal approach for off‐label use of SGLT‐2 inhibitors involves only including patients with a baseline HbA1c less than 9%, baseline ketone levels below 0.6 mmol/L, starting SGLT‐2 inhibitor treatment at the lowest dose, not changing insulin dosage, and continuing with morning ketone testing until the maximum, stable dose is reached.…”
Section: Practical Ways To Achieve Targets In Diabetes Care Conferencementioning
confidence: 99%